Magnetic Mesoporous Silica Nanoparticles Functionalized with 5,5′-Dithiobis(2-Nitrobenzoic Acid) for Highly Efficient Removal of Organic Dyes from Contaminated Water - Abeer Beagan; Shrooq Khibari; Abdullah Alswieleh (Journal of Chemistry, 2023)
The removal of organic pollutants has become an increasingly important environmental concern. In recent years, there has been significant research into the use of nanomaterials for removing organic dyes in single-component systems. In this study, magnetic mesoporous silica nanoparticles (magnetic MSNs) were prepared with an average particle size of 170 nm. Iron oxide nanoparticles (20 nm) were embedded within the mesoporous silica structure. These nanoparticles were functionalized with amine, derivatized with thiol, and then reacted with 5,5′-dithiobis-(2-nitrobenzoic acid) (DTNB). The presence of DTNB molecules attached to the surface was confirmed by FTIR spectra, as evidenced by the appearance of peaks at ∼1528 cm−1 and ∼1365 cm−1. The nanoadsorbents demonstrated high removal efficiency for bromothymol blue (BT) and methyl orange (MO) at a pH below 5, with a maximum adsorption capacity of 139.27 mg/g and 101.62 mg/g for BT and MO, respectively. The linear regression coefficient value suggested that the adsorption of BT and MO onto magnetic MSNs-DTNB followed the Langmuir isotherm and second-order process. Overall, these findings suggest that magnetic MSNs-DTNB could be a promising nanoadsorbent for removing organic pollutants from contaminated water sources.